2018
DOI: 10.1108/gkmc-10-2017-0086
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge management in providing innovative services in university libraries in Nigeria

Abstract: Purpose Previous studies have shown that knowledge management (KM) plays a role in service innovation or that there is a positive relationship between them. However, this role or relationship is yet to be established quantitatively through empirical evidence within the context of university libraries in Nigeria. The purpose of this study is to determine how knowledge management affects innovative services in university libraries in Nigeria. Design/methodology/approach The study adopted a quantitative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
2
16
0
1
Order By: Relevance
“…The study found that the knowledge management activities have significant influence on innovation practices. This finding supports the declaration by Rahman et al (2009a); Andreeva and Kianto (2011); Gloet and Terziovski (2004); Huang and Li (2009) and Ugwu and Ekere (2018) that firms with high level of actions in knowledge management practices are more likely to offer innovative products and services to their customers. This is explained by the fact that acquiring or creating knowledge from different sources is an important aspect of innovation in the firms.…”
Section: Discussionsupporting
confidence: 89%
“…The study found that the knowledge management activities have significant influence on innovation practices. This finding supports the declaration by Rahman et al (2009a); Andreeva and Kianto (2011); Gloet and Terziovski (2004); Huang and Li (2009) and Ugwu and Ekere (2018) that firms with high level of actions in knowledge management practices are more likely to offer innovative products and services to their customers. This is explained by the fact that acquiring or creating knowledge from different sources is an important aspect of innovation in the firms.…”
Section: Discussionsupporting
confidence: 89%
“…the implications of KM for LIS professions (Sarrafzadeh, 2008); when existing and emerging disciplines meet: LIS versus KM (Roknuzzaman, 2009); a case study of LIS schools using KM (Islam, 2012) and KM for innovation in library services (Islam, 2016). Researchers have carried our empirical studies advocating adopting KM in libraries: KM practices in European university libraries (Balagué et al , 2016); effect of KM and service innovation in academic libraries (Islam et al , 2017); KM readiness of academic libraries (Marouf, 2017); KM for innovative services in university libraries (Ugwu and Ekere, 2018); expected librarian KM roles (AbuKhader, 2018) and innovation in academic libraries through knowledge creation (Koloniaria et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…All three of those phases within the KM cycle have an impact on the level of innovation in the services provided within academic libraries (Islam et al (2017). There is some discussion as to whether knowledge sharing had a noticeable impact on innovation (Islam et al, 2017), but more localised studies have found that all three phases of the KM cycle do contribute to innovation, albeit on a lower scale than phase one and three of the KM cycle (Ugwu & Ekere, 2017).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In the second stage of the KM cycle, ICTs "facilitate the rapid collection, storage, and use of explicit knowledge [...] and enhances knowledge sharing and creation" (Koloniari et al, 2018, p.794). Ugwu & Ekere (2017) also emphasized the importance of understanding the tools available to the staff that can increase innovation and service quality. In their study, focusing on university libraries in Nigeria, they found that the main activities that supported innovation included learning about new practices, user interfaces, and the application of new technology to meet the needs of the students and staff.…”
mentioning
confidence: 99%